Endoscopic Procedures in Patients under Clopidogrel or Dual Antiplatelet Therapy: A Survey among German Gastroenterologists and Current Guidelines - Abdel Samie, A.; Theilmann, L.; Labenz, J. (Zeitschrift für Gastroenterologie, 2014)
Background: Because of the higher risk of bleeding, guidelines recommend cessation of clopidogrel seven days prior to high-risk endoscopic procedures. However, premature cessation of clopidogrel may lead to catastrophic cardiovascular sequelae due to stent thrombosis. We aimed to assess the current clinical practice among German gastroenterologists regarding endoscopic procedures in patients under clopidogrel/dual antiplatelet therapy.Methods: A 10-item questionnaire on endoscopic procedures in patients under clopidogrel/dual antiplatelet therapy was sent by e-mail to all 220 members of the ALGK.Results: 73 (33 %) chief gastroenterologists returned completed questionnaires, 35 (48 %) of whom conduct high-volume endoscopic units performing more than 4000 procedures per annum. 62 (85 %) endoscopic units perform endoscopic biopsies under clopidogrel alone, while just in 30 (41 %) departments biopsies are carried out under dual antiplatelet therapy. In 36 (49 %) GI-units endoscopic polypectomy under clopidogrel monotherapy is performed, in contrast to only 4 (5.5 %) in the case of combined antiplatelet therapy. However, in emergency situations more than 60 % of all participants do perform endoscopic sphincterotomy in patients under clopidogrel/dual antiplatelet therapy. Percutaneous endoscopic gastrostomy is carried out in 32 endoscopic units (44 %) under clopidogrel monotherapy, but only in 4 (5.5 %) under dual antiplatelet therapy.Conclusion: Current guidelines on endoscopic procedures in patients under clopidogrel/dual antiplatelet therapy are mainly based on expert opinion and therefore, backed by only weak evidence. Our survey shows that in this setting the clinical decision making takes place on an individual basis, as there are no data to support the recommendations of the present guidelines.
Keywords: Thrombozytenaggregationshemmung; Clopidogrel; endoskopischen Prozeduren; Fragebogen